2022
DOI: 10.1007/s10143-022-01851-y
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of the “No ICU – Unless” approach in postoperative neurosurgical management in times of COVID-19

Abstract: Following elective craniotomy, patients routinely receive 24-h monitoring in an intensive care unit (ICU). However, the benefit of intensive care monitoring and treatment in these patients is discussed controversially. This study aimed to evaluate the complication profile of a “No ICU – Unless” strategy and to compare this strategy with the standardized management of post-craniotomy patients in the ICU. Two postoperative management strategies were compared in a matched-pair analysis: The first cohort included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Among these are comorbidities such as cardiovascular disease, diabetes, higher age, surgery-associated aspects (e.g., duration, blood loss, vasopressor therapy), tumor size, or certain surgical positions. However, the inclusion criteria vary greatly; some studies include patients with infratentorial tumors [ 2 – 5 , 17 , 20 ], while others include stereotactical biopsies and/or transsphenoidal approaches which carry a different postoperative risk [ 4 , 10 , 16 , 20 , 21 ]. Sometimes, the protocols for patients not transferred to ICU include hourly neurological exams performed by nurses and continuous or hourly monitoring of vital parameters which might not be possible in every hospital due to a lower nurse-to-patient ratio [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are comorbidities such as cardiovascular disease, diabetes, higher age, surgery-associated aspects (e.g., duration, blood loss, vasopressor therapy), tumor size, or certain surgical positions. However, the inclusion criteria vary greatly; some studies include patients with infratentorial tumors [ 2 – 5 , 17 , 20 ], while others include stereotactical biopsies and/or transsphenoidal approaches which carry a different postoperative risk [ 4 , 10 , 16 , 20 , 21 ]. Sometimes, the protocols for patients not transferred to ICU include hourly neurological exams performed by nurses and continuous or hourly monitoring of vital parameters which might not be possible in every hospital due to a lower nurse-to-patient ratio [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qasem et al . [ 25 ] also observed that most complications occur 24 h postoperatively. Further, the mean length of hospital stay in our study was relatively prolonged (17.86 days) due to COVID-19-related transfer delays within the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Under the impression of possible complications of an ICU admission, the repelling impression of an "apparatus medicine" as well as the increasing financial/capacity pressure, an increasing avoidance of postoperative ICU monitoring has recently gained interest [18][19][20]. However, the (desired) reduction of postoperative ICU monitoring mandates a detailed and individualized consideration of the patient's risk/benefit profile in order to weigh the safety of postoperative monitoring against unnecessary ICU treatment [21].…”
Section: Discussionmentioning
confidence: 99%